Handbook of terahertz technology for imaging, sensing and communications - Saeedkia, Daryoosh (Woodhead Publishing series in electronic and optical materials., 2013)
The recent development of easy-to-use sources and detectors of terahertz radiation has enabled growth in applications of terahertz (Thz) imaging and sensing. This vastly adaptable technology offers great potential across a wide range of areas, and the Handbook of terahertz technology for imaging, sensing and communications explores the fundamental principles, important developments and key applications emerging in this exciting field. Part one provides an authoritative introduction to the fundamentals of terahertz technology for imaging, sensing and communications. The generation, detection and emission of waves are discussed alongside fundamental aspects of surface plasmon polaritons, terahertz near-field imaging and sensing, room temperature terahertz detectors and terahertz wireless communications. Part two goes on to discuss recent progress and such novel techniques in terahertz technology as terahertz bio-sensing, array imagers, and resonant field enhancement of terahertz waves. Fiber-coupled time-domain spectroscopy systems (THz-TDS), terahertz photomixer systems, terahertz nanotechnology, frequency metrology and semiconductor material development for terahertz applications are all reviewed. Finally, applications of terahertz technology are explored in part three, including applications in tomographic imaging and material spectroscopy, art conservation, and the aerospace, wood products, semiconductor and pharmaceutical industries. With its distinguished editor and international team of expert contributors, the Handbook of terahertz technology for imaging, sensing and communications is an authoritative guide to the field for laser engineers, manufacturers of sensing devices and imaging equipment, security companies, the military, professionals working in process monitoring, and academics interested in this field. Examines techniques for the generation and detection of terahertz wavesDiscusses material development for terahertz applicationsExplores applications in tomographic imaging, art conservation and the pharmaceutical and aerospace industries.